Analysis of Factors in Efforts to Improve Operational Performance (Study on Clamp Ring Production at PT Pramesta Baja Utama) - Haikal, Muhamad; Purwanto, Setiyo (Journal of Accounting and Finance Management, 2024)
This research aims to determine and analyze the simultaneous influence of supply chain management, innovation strategies, and total quality management on operational performance in clamp ring production at PT. Pramesta Baja Utama. The method used in this research is a quantitative descriptive method. Data processing was conducted using statistical analysis with a regression model aided by SPSS 26. The sampling method used was saturated sampling, where all members of the population were included as samples. In this study, the sample consisted of 100 employees as respondents. The tests conducted included instrument feasibility tests, classical assumption tests, partial T-tests, simultaneous F-tests, and determination coefficients. It was found that supply chain management had an influence on operational performance in clamp ring production at PT. Pramesta Baja Utama, but the effect was not significant. Based on various analyses and data processing conducted to explore the factors that contribute to improving operational performance, it can be concluded that supply chain management, innovation strategies, and total quality management have a positive and significant simultaneous impact on the operational performance of clamp ring production.